Degradable magnesium alloy anastomosis nail and preparation process thereof

CN122894564APending Publication Date: 2026-10-13SHANGHAI JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611398186.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但发明人发现,其作为永久性异物存留于体内,会导致慢性肉芽肿炎症、吻合口狭窄以及严重的CT/MRI影像伪影掩盖病灶;且惰性金属吻合钉无法降解,对于儿童患者或需二次手术的病例,取钉过程极易造成组织二次损伤;而“B”型吻合钉高压紧力虽然能止血,但常导致夹持区域微血管完全闭塞,引发局部缺血坏死,甚至造成致死性的“吻合口瘘”

Benefits of technology

[0019]本发明的实施例提供的技术方案带来的有益效果是:本发明实施例的吻合钉的横梁与并拢的钉腿形成了一个类似半圆形的D型闭环结构,结合吻合钉的组成成分可实现在保持闭合强度的前提下夹持组织时,为粘膜下层毛细血管预留约20 %~30 %的扩张空间,避免对毛细血管网的绝对阻断,显著降低了术后吻合口边缘组织坏死和吻合口瘘的概率。本发明实施例的制备方法对Mg-Nd-Y-Zr合金在热挤压与热处理后能析出弥散的纳米级第二相(如Mg12Nd和Mg24Y5相),通过Zr元素的晶粒细化作用,将晶粒尺寸细化至8 μm以下,使本发明实施例制备的吻合钉初始屈服强度达到240 MPa以上的同时可实现锋利穿刺,其室温延伸率保持在12%以上甚至更大,使吻合器抵钉座中发生大角度弯折成D型时不断裂且不产生微裂纹。且热处理消除了晶界处的第二相偏析,减少了微电偶腐蚀位点,使制备的吻合钉在植入人体28天后,其残余强度仍能维持在初始值的85 %以上,且降解产物(Mg2+、Nd3+等)具有良好的生物相容性,对后续影像学复查不造成任何影响。而添加的稀土元素Y元素能在镁合金表面促成致密且具有保护作用的氧化膜Y2O3膜层,极大延缓了材料在早期点蚀的发生,与纯镁在7天内丧失强度比较,本发明实施例的方法制备的吻合钉能在植入体内28天时的初始拉伸强度依然保持在 85%~92% 之间,完美覆盖肠道组织的愈合危险期。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894564A_ABST
    Figure CN122894564A_ABST
Patent Text Reader

Abstract

The embodiment of the application discloses a degradable magnesium alloy anastomosis nail and a preparation process thereof, the D-shaped closed loop structure of the anastomosis nail reserves a certain expansion space for submucosal capillary vessels, avoids absolute blockage of the capillary vessel network, and significantly reduces the occurrence of postoperative anastomosis edge tissue necrosis and anastomosis fistula. Hot extrusion and heat treatment make the Mg-Nd-Y-Zr matrix phase precipitate a dispersed nanoscale second phase, combined with the grain refinement effect of the Zr element, the grain size is refined to below 8 microns; artificial aging makes the precipitated phase stay in the high-density distribution stage of the beta phase, prevents grain boundary embrittlement, realizes the large initial yield strength of the anastomosis nail while sharp puncture, and the room temperature elongation is always effectively maintained above 12%. And the heat treatment process eliminates the second phase segregation at the grain boundary, reduces the micro galvanic corrosion site, and the Y element promotes the Y2O3 film layer on the magnesium alloy surface, greatly delays the occurrence of early pitting of the material, so that the prepared anastomosis nail can effectively maintain the residual strength after implantation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, specifically to a biodegradable magnesium alloy anastomosis staple for medical use and its preparation process. Background Technology

[0002] In gastrointestinal surgery, the quality of digestive tract reconstruction directly affects the patient's postoperative survival rate. In related techniques, the main materials used clinically for anastomotic staples are medical-grade titanium alloys (such as Ti-6Al-4V) and stainless steel, which have excellent mechanical properties, and the staples are shaped like a "B". However, the inventors discovered that as permanent foreign bodies remaining in the body, they can lead to chronic granulomatous inflammation, anastomotic stenosis, and severe CT / MRI image artifacts that obscure the lesion. Furthermore, inert metal staples are non-degradable, and the staple removal process can easily cause secondary tissue damage in pediatric patients or cases requiring secondary surgery. While the high-pressure clamping force of the "B"-type staples can stop bleeding, it often leads to complete occlusion of microvessels in the clamping area, causing local ischemic necrosis and even fatal "anastomotic leakage". Summary of the Invention

[0003] To address the aforementioned technical problems, embodiments of the present invention provide a biodegradable anastomotic staple with high initial puncture strength, a degradation rate matching the intestinal healing cycle, and without affecting local microcirculation, combined with an ischemia-resistant D-type structure Mg-Nd-Y-Zr quaternary alloy system and its preparation method.

[0004] An embodiment of the present invention provides a biodegradable magnesium alloy staple, wherein the staple matrix is ​​a quaternary magnesium alloy of Mg-Nd-Y-Zr, and its composition by mass percentage (wt%) is as follows: Nd (neodymium) 2.0%~4.0%, Y (yttrium) 0.5%~3.0%, Zr (zirconium) 0.3%~0.8%, unavoidable impurities total less than 0.02%, and the remainder is Mg (magnesium); the staple is U-shaped in the initial assembly state, and after being formed by the stapler, its shape is transformed into a closed D-shaped structure. The D-shaped structure is formed by the inward curling of the staple legs at both ends of the U-shape and the ends abutting or overlapping, and its longitudinal height after closure is less than the initial length of the staple legs of the U-shaped structure.

[0005] Furthermore, the pre-firing structure of the staple is U-shaped, and the U-shaped structure consists of a straight crossbeam and staple legs integrally connected to both ends of the crossbeam and perpendicular to the crossbeam.

[0006] Furthermore, the end of the U-shaped stud leg of the anastomotic staple is provided with a chamfer and a puncture tip before firing, and the chamfer angle is 30° to 45°.

[0007] Furthermore, the length of the crossbeam of the U-shaped structure before the anastomotic staple is 3.0 mm to 5.0 mm, the length of the staple leg is 3.5 mm to 5.5 mm, and the diameter of the staple wire is 0.2 mm to 0.4 mm.

[0008] This invention provides a process for preparing biodegradable magnesium alloy staples, comprising the following steps:

[0009] (1) Determine the proportion of raw materials, wherein the raw materials include high-purity magnesium ingots, Mg-Nd master alloy, Mg-Y master alloy, and Mg-Zr master alloy, and prepare the raw materials according to the mass percentage of the target alloy;

[0010] (2) Vacuum induction melting and casting: The prepared raw materials are placed in the crucible of the vacuum induction melting furnace, and after vacuuming, protective gas is introduced. Melting is carried out at a temperature of 720 ℃~760 ℃, with mechanical stirring for 15 minutes. Then, the mixture is poured into a preheated steel mold to obtain an alloy ingot.

[0011] (3) Homogenization heat treatment: Place the above alloy ingot in a heat treatment furnace and heat it to 500°C at a heating rate of 5°C / min under a protective atmosphere. Hold it for 8 hours. After holding, take it out and air cool it to room temperature.

[0012] (4) Hot extrusion and multi-pass cold drawing: The homogenized ingot is processed into an extrusion billet, heated to 350℃ and held for 2 hours, and extruded into a bar at an extrusion ratio of 18:1 on an extrusion press. The extrusion speed is controlled at 0.5 to 2.0 m / min. The extrusion bar is drawn through multiple dies. The deformation amount of each drawing is controlled between 10% and 20%. Intermediate annealing at 300℃ to 350℃ for 60 minutes is required between passes to obtain wire with a diameter of 0.2 mm to 0.4 mm.

[0013] (5) Graded solution treatment and artificial aging treatment: The wire is placed in a tube resistance furnace and heated to 480°C under argon protection. After holding at this temperature for 2 hours, the temperature is raised to 520°C and held for 2 hours. Then, it is quickly taken out and water-quenched to room temperature. The water-quenched wire is placed in an aging furnace and held at 225°C for 24 hours. Then, it is air-cooled to room temperature.

[0014] (6) Stamping and forming: the aged wire is cut into lengths of 3.5mm to 5.5mm, and then stamped and bent into a "D"-shaped initial state anastomosis nail at room temperature through a forming mold, and the surface is ultrasonically cleaned; after cleaning, the initial state anastomosis nail is squeezed by the anastomosis device, and the two nail legs are curled and bent towards the center of the inner crossbeam, and the ends of the two nail legs abut or overlap each other to form a "D"-shaped closed structure anastomosis nail.

[0015] It should be noted that the anastomotic staple prepared in this embodiment has the above-mentioned U-shaped structure before firing (i.e., the initial form); in actual surgical applications, the U-shaped anastomotic staple is loaded in the staple cartridge of the stapler. After firing, the two legs of the U-shaped structure are guided and squeezed by the stapler's abutment seat, and curled and bent towards the center of the inner crossbeam. The ends of the two legs abut or overlap each other, thereby undergoing plastic deformation to form a D-shaped shape (i.e., a closed-structure anastomotic staple).

[0016] Furthermore, in step (2), high-purity argon is used as a protective gas.

[0017] Further, in step (5), the graded solution treatment is divided into primary solution treatment and secondary solution treatment. In the primary solution treatment, the drawn rivet wire is placed in a tubular resistance furnace and heated to 480°C under argon protection and held for 2 hours. In the secondary solution treatment, the furnace temperature is raised to 520°C based on the primary solution treatment and held for 2 hours. Then, it is quickly taken out and water quenched to room temperature.

[0018] Furthermore, in step (5), the water quenching temperature is 60 ℃~80 ℃.

[0019] The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows: The crossbeam and the converging legs of the anastomotic staple in the embodiments of the present invention form a semi-circular D-shaped closed-loop structure. Combined with the components of the anastomotic staple, it can achieve the goal of retaining approximately 20% to 30% expansion space for submucosal capillaries while clamping tissue, while maintaining closure strength. This avoids absolute blockage of the capillary network and significantly reduces the probability of postoperative anastomotic edge tissue necrosis and anastomotic leakage. The preparation method of the embodiments of the present invention can precipitate dispersed nanoscale second phases (such as Mg) in Mg-Nd-Y-Zr alloys after hot extrusion and heat treatment. 12 Nd and Mg 24 The Y5 phase, through the grain-refining effect of Zr, refines the grain size to below 8 μm, enabling the anastomosis staples prepared in this embodiment to achieve an initial yield strength of over 240 MPa while achieving sharp puncture. Its room temperature elongation remains above 12% or even greater, preventing fracture and microcrack formation when the staple seat is bent into a D-shape at a large angle. Furthermore, heat treatment eliminates second-phase segregation at grain boundaries and reduces microgalvanic corrosion sites, allowing the prepared anastomosis staples to maintain a residual strength of over 85% of its initial value 28 days after implantation. The degradation products (Mg...) 2+ 、Nd 3+(etc.) It has good biocompatibility and does not affect subsequent imaging follow-up. The added rare earth element Y can promote a dense and protective Y2O3 oxide film on the surface of the magnesium alloy, which greatly delays the occurrence of early pitting corrosion. Compared with the loss of strength of pure magnesium within 7 days, the anastomosis staple prepared by the method of this embodiment can still maintain an initial tensile strength of 85%~92% after 28 days of implantation, perfectly covering the critical period of intestinal tissue healing. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the magnesium alloy staple of the present invention; Figure 2 The room temperature tensile stress-strain curves of the Mg-2.5Nd-0.5Zr alloy wire (without Y element) prepared in Comparative Example 2 are shown; where HENG 1~3 are transverse samples (perpendicular to the extrusion direction) and ZONG 1~3 are longitudinal samples (parallel to the extrusion direction). Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be further described below with reference to the accompanying drawings.

[0022] Example 1

[0023] Embodiments of the present invention provide a biodegradable magnesium alloy staple, such as Figure 1 As shown, the staple matrix is ​​a quaternary magnesium alloy of Mg-Nd-Y-Zr, and its composition by mass percentage (wt%) is as follows: Nd (neodymium) 2.0%~4.0%, Y (yttrium) 0.5%~3.0%, Zr (zirconium) 0.3%~0.8%, unavoidable impurities totaling less than 0.02%, and the remainder being Mg (magnesium). The staple has a D-shaped structure after firing. The D-shaped closed structure is formed by the deformation of the U-shaped structure before firing through the compression of the stapler's anvil. The final size of its inner ring space is determined by the initial length of the U-shaped crossbeam, the length of the staple leg, and the geometry of the stapler's anvil.

[0024] The anastomotic staples of this invention combine rare earth elements with magnesium. Nd is the core strengthening element in the anastomotic staples of this invention. It has a large solid solubility in magnesium, which decreases sharply with decreasing temperature, resulting in significant solid solution strengthening and age-induced precipitation strengthening, providing a significant age-hardening response. When its content is below 2.0%, the strengthening effect is not obvious; above 4.0%, it easily forms coarse eutectic phases, drastically reducing plasticity. Y is the core element for improving corrosion resistance, and it synergistically precipitates strengthening phases with Nd and generates a highly stable surface passivation film. When its content is below 0.5%, the improvement in corrosion resistance is limited; above 3.0%, it increases the risk of cytotoxicity. Zr acts as a grain refiner, effectively refining the grains in both cast and extruded states, improving the strength and toughness of the material, and inhibiting grain coarsening during subsequent heat treatment.

[0025] Preferably, the raw material composition of the anastomotic staple is as follows by mass percentage (wt%): Nd 2.5wt%, Y 1wt%, Zr 0.5wt%, with the balance being Mg.

[0026] Preferably, the ends of the two legs of the D-shaped closed anastomotic staple overlap after anastomosis. The area preserved within the ring meets the microvascular perfusion requirements.

[0027] Preferably, the unavoidable impurities include heavy metal elements such as Fe, Cu, and Ni that are highly susceptible to galvanic corrosion, and their individual content must be controlled below 0.005%.

[0028] Preferably, the pre-firing structure of the anastomotic staple is U-shaped, wherein the U-shaped structure consists of a straight crossbeam and staple legs integrally connected to both ends of the crossbeam and perpendicular to the crossbeam.

[0029] Preferably, the end of the U-shaped stud leg of the anastomotic staple is provided with a chamfer and a puncture tip before firing, and the chamfer angle is 30° to 45°.

[0030] Preferably, the length of the crossbeam of the U-shaped structure before the staple is fired is 3.0 mm to 5.0 mm, the length of the staple leg is 3.5 mm to 5.5 mm, and the diameter of the staple wire is 0.2 mm to 0.4 mm.

[0031] This invention also provides a method for preparing a biodegradable magnesium alloy staple, comprising the following steps: (1) Determine the proportion of raw materials: The raw materials include high-purity magnesium ingots, Mg-Nd master alloy, Mg-Y master alloy, and Mg-Zr master alloy. The raw materials are prepared according to the mass percentage of the target alloy. In this embodiment of the invention, considering the burn-off rate of rare earth elements during the smelting process, when preparing 6kg alloy melt by weighing and batching, the amount of Nd and Y elements needs to be increased by 40% to 50% of the burn-off compensation weight based on the theoretical calculation value, and the amount of Zr element needs to be increased by 100% to 120% of the burn-off compensation weight. The balance is high-purity magnesium (purity 99.95%). (2) Vacuum induction melting and casting: The prepared raw materials are placed in the crucible of the vacuum induction melting furnace, and after vacuuming, protective gas is introduced. Melting is carried out at a temperature of 720 ℃~760 ℃, with mechanical stirring for 15 minutes. Then, the mixture is poured into a preheated steel mold to obtain an alloy ingot. Specifically, the protective gas is high-purity argon (purity ≥ 99.99%).

[0032] (3) Homogenization heat treatment: The above alloy ingot is placed in a heat treatment furnace and heated to 500°C at a heating rate of 5°C / min under a protective atmosphere. It is held for 8 hours. After the holding period, it is taken out and air-cooled to room temperature. The homogenization heat treatment process eliminates dendritic segregation in the as-cast structure and allows the non-equilibrium eutectic phase to dissolve into the magnesium matrix as much as possible. (4) Hot extrusion and multi-pass cold drawing: The homogenized ingot is hot extruded into an extrusion billet, heated to 350℃ and held for 2 hours, and then extruded into a bar at an extrusion ratio of 18:1 on an extrusion press. The extrusion speed is controlled at 0.5 to 2.0 m / min. The extrusion bar is drawn through multiple dies. The deformation of each drawing is controlled between 10% and 20%. The temperature between each pass is 300℃ to 350℃ and held for 60 minutes. Intermediate annealing is used to obtain a matching nail wire with a diameter of 0.2 mm to 0.4 mm. The intermediate annealing process can eliminate work hardening. (5) Graded solution treatment and artificial aging treatment: The mating nail wire is placed in a tube resistance furnace and heated to 480°C under argon protection. After holding at this temperature for 2 hours, the temperature is raised to 520°C and held for 2 hours. Then, it is quickly taken out and water-quenched to room temperature. The water-quenched wire is placed in an aging furnace and held at 225°C for 24 hours. Then, it is air-cooled to room temperature. Graded solution treatment can initially dissolve the residual coarse second phase, avoid grain boundary overburning caused by rapid temperature rise, and allow rare earth strengthening elements to fully dissolve into the magnesium matrix to obtain a supersaturated solid solution. Artificial aging treatment can promote the precipitation of a large amount of nanoscale dispersed strengthening phase, which can significantly improve the bending plasticity of the material while ensuring the yield strength. Specifically, the graded solution treatment is divided into primary solution treatment and secondary solution treatment. In the primary solution treatment, the drawn ferrule wire is placed in a tube resistance furnace and heated to 480°C under argon protection, and held at that temperature for 2 hours. The purpose of the primary solution treatment stage is to allow the low-melting-point Mg-Nd binary eutectic structure to dissolve slowly at a safe temperature, avoiding local liquefaction of grain boundaries (i.e., overheating) due to excessively rapid heating. The secondary solution treatment involves raising the furnace temperature to 520°C based on the primary solution treatment, holding it at that temperature for 2 hours, and then quickly removing it for water quenching to room temperature. The secondary solution treatment stage allows the Y element to fully dissolve into the matrix at a high temperature, maximizing the solid solution strengthening effect. Specifically, the water quenching temperature is 60℃~80℃; warm water quenching provides a sufficient cooling rate to retain the supersaturated solid solution, while effectively reducing the internal residual stress of the fine wires and preventing subsequent fracture. Artificial aging, by controlling the time, keeps the precipitated phase at the β (acicular Mg) stage. 12 The high-density distribution stage of the Nd phase should be avoided to prevent the transition to the β equilibrium phase (coarse and massive) stage, thus preventing grain boundary embrittlement.

[0033] (6) Stamping and forming: the aging-treated staple wire is cut into lengths of 3.5mm to 5.5mm, and stamped and bent into a "D"-shaped initial state staple at room temperature using a forming mold, and the surface is ultrasonically cleaned; after cleaning, the initial state staple is squeezed by the stapler seat, and the two staple legs curl and bend towards the center of the inner crossbeam, and the ends of the two staple legs abut or overlap each other to form a D-shaped closed structure staple.

[0034] Preferably, step (4) uses equal channel corner extrusion instead of hot extrusion to refine the grains to the submicron level. This also reduces the heat treatment time.

[0035] Preferably, the D-type closed-structure staple has an elliptical cross-section or a circular cross-section with longitudinal reinforcing ribs. After heat treatment, it has certain strength advantages and can further improve bending resistance.

[0036] Example 2

[0037] This invention provides a method for preparing a biodegradable magnesium alloy staple, comprising the following steps: (1) Determine the raw material ratio and prepare the raw materials according to the target alloy Mg-2.5 Nd-1 Y-0.5 Zr by mass percentage; (2) Vacuum induction melting and casting: The prepared raw materials are placed in the crucible of the vacuum induction melting furnace, and after vacuuming, protective gas is introduced. The melting is carried out at a temperature of 750°C, and mechanical stirring is performed for 15 minutes. Then, the mixture is poured into a preheated steel mold to obtain an alloy ingot. (3) Homogenization heat treatment: Place the above alloy ingot in a heat treatment furnace and heat it to 450°C at a heating rate of 5°C / min under a protective atmosphere. Hold it for 10 hours. After holding, take it out and air cool it to room temperature. (4) Hot extrusion and multi-pass cold drawing, wherein hot extrusion processes the homogenized ingot into an extrusion billet, heats it to 350°C and holds it for 2 hours, and then extrudes it into a bar at an extrusion ratio of 18:1 on an extrusion press, with the extrusion speed controlled at 0.5 to 2.0 m / min; cold drawing draws the extrusion bar through multiple dies, with the deformation amount controlled between 10% and 20% for each drawing, and intermediate annealing at 300°C to 350°C for 60 minutes between passes is required to obtain a matching nail wire with a diameter of 0.3 mm; (5) Graded solution treatment and artificial aging treatment: The matching nail wire is placed in a tube resistance furnace and heated to 480°C under argon protection. After holding at this temperature for 2 hours, the temperature is raised to 520°C and held for 2 hours. Then, it is quickly taken out and water-quenched to room temperature. The water-quenched wire is placed in an aging furnace and held at 225°C for 24 hours. Then, it is air-cooled to room temperature. (6) Stamping: The aged staple wire is cut into lengths of 3.5mm to 5.5mm, and stamped and bent into a "D"-shaped initial state staple at room temperature using a forming die. The surface is then ultrasonically cleaned. After cleaning, the initial state staple is pressed by the stapler's anvil, and the two staple legs curl and bend towards the center of the inner crossbeam. The ends of the two staple legs abut or overlap each other to form a D-shaped closed structure staple. The rest is the same as in Example 1.

[0038] The mechanical properties of the anastomotic staples prepared in this embodiment of the invention are: yield strength (YS) 302 MPa, tensile strength (UTS) 341 MPa, and elongation 19%.

[0039] After the anastomotic staples prepared in the embodiments of the present invention were dynamically immersed in simulated artificial intestinal fluid (pH=6.8, 37℃) for 28 days, the residual tensile strength was measured to be 319 MPa (the retention rate was 91% of the original strength). The average corrosion rate of the anastomotic staples in the simulated intestinal fluid decreased to 0.148 mm / year, which fully meets the medical requirement that gastrointestinal anastomotic staples need to be stably supported for at least 2 weeks.

[0040] Comparative Example 1 In this embodiment of the invention, the target alloy Mg-2.5Nd-2.5Y-0.5Zr was prepared by formulating the raw materials according to the mass percentage of the target alloy. The rest is the same as in Example 2.

[0041] The anastomotic staples prepared in this embodiment of the invention have a high Y content, and their mechanical properties are: yield strength (YS) 324 MPa, tensile strength (UTS) 356 MPa, and elongation 12%. Due to the excessively high Y content, a large number of coarse, continuous network-like second phases (Mg) precipitated at the grain boundaries. 24 Although the hardness of Y5 is further improved, the brittleness of the material increases dramatically and the elongation decreases significantly.

[0042] After the anastomotic nails prepared in this embodiment of the invention were dynamically immersed in simulated artificial intestinal fluid (pH=6.8, 37℃) for 28 days, the strength retention rate was only 52% of the original strength. This indicates that excessive rare earth phases formed strong galvanic corrosion between the rare earth phases and the magnesium matrix. During the dynamic immersion process, the second phase at the grain boundaries preferentially dissolved, leading to severe intergranular corrosion. Although the initial strength was high, the structure became porous in the later stages of corrosion, failing to provide effective closure support.

[0043] Comparative Example 2 In this embodiment of the invention, the target alloy Mg-2.5 Nd-0.5 Zr was prepared by formulating the raw materials according to the mass percentage of the target alloy. The rest is the same as in Example 2.

[0044] The mechanical properties of the anastomotic staples prepared according to the embodiments of the present invention are: yield strength (YS) 232 MPa, tensile strength (UTS) 253 MPa, and elongation 16%.

[0045] After dynamic immersion in simulated intestinal fluid (pH=6.8, 37℃) for 28 days, the anastomotic staples prepared in this embodiment of the invention retained only 62% of their original strength, failing to guarantee the mechanical safety of the anastomosis in the later stages of tissue healing. The anastomotic staples of this embodiment lack the repairing effect of Y element, resulting in a relatively loose oxide film. During the dynamic immersion process, significant hydrogen evolution corrosion and pitting occurred in localized areas, leading to a substantial reduction in the effective load-bearing cross-sectional area.

[0046] Standard tensile specimens were cut from the aged wire along both the transverse (perpendicular to the extrusion direction, denoted as HENG) and longitudinal (parallel to the extrusion direction, denoted as ZONG) directions. Room temperature tensile properties were tested according to GB / T 228.1-2021 "Metallic materials, tensile testing—Part 1: Tests at room temperature," with a test temperature of 23 ℃ ± 2 ℃, a tensile rate of 1 mm / min, and a gauge length of 50 mm. Three parallel samples were tested in each direction, for a total of six groups. The stress-strain curves are shown below. Figure 2 As shown, the specific test results are shown in Table 1. Table 1: Room temperature tensile properties test results of alloy wire from Comparative Example 2.

[0047] Table 1. Room temperature tensile properties of alloy wire from Comparative Example 2

[0048] Depend on Figure 2 As shown in Table 1, the average yield strength of the alloy wire in Comparative Example 2 was 232 MPa, the average tensile strength was 249.7 MPa, and the average elongation at break was 12.97%. The mechanical properties of the transverse sample (HENG) showed significant dispersion (standard deviation 13.4 MPa), with HENG 1 exhibiting a yield strength of only 208 MPa, significantly lower than the longitudinal sample, indicating a pronounced anisotropy in the absence of Y element. After dynamic immersion in simulated artificial intestinal fluid (pH=6.8, 37℃) for 28 days, the anastomotic staples prepared in this embodiment of the invention retained only 62% of their original strength, failing to guarantee the mechanical safety of the anastomosis in the later stages of tissue healing. The anastomotic staples in this embodiment lacked the repairing effect of Y element, resulting in a relatively loose oxide film. During dynamic immersion, significant hydrogen evolution corrosion and pitting occurred in localized areas, leading to a substantial reduction in the effective load-bearing cross-sectional area.

[0049] Comparative Example 3 Existing methods use 99.99% high-purity magnesium wire to prepare staples of the same size.

[0050] The prepared anastomotic staples had a yield strength of only 82 MPa, and when penetrating simulated multi-layered porcine intestinal tissue, they exhibited beam bending deformation (failing to penetrate smoothly), with a puncture failure rate exceeding 65%. After being immersed in simulated artificial intestinal fluid for 14 days, the surface underwent severe peeling and powdering, making the anastomosis site highly susceptible to rupture.

[0051] Comparative Example 4 The target alloy Mg-2.5 Nd alloy was prepared using the method of Example 2 of the present invention, and the rest was the same as in Example 2.

[0052] The prepared anastomotic staples, lacking the grain-refining effect of Zr, had an average grain size as high as 80-120 μm. The coarse grains resulted in an elongation of only 7%, and when fired into a D-shape, the fracture rate at the bend of the staple leg was as high as 45%. Furthermore, lacking the protection of Y element, after being immersed in simulated artificial intestinal fluid for 28 days, its residual strength after degradation was only 35%.

[0053] Comparative Example 5 Existing methods are used to prepare pure titanium type B anastomotic staples.

[0054] The prepared anastomotic staples are extremely strong and do not degrade. In a live animal (miniature pig) end-to-end intestinal anastomosis experiment, pathological sections on the 7th day after surgery showed that the pure titanium type B staple clamping area had obvious capillary blockage and mild tissue necrosis; while the magnesium alloy type D staple used in Example 1 showed good microvascular perfusion in the clamping area and no signs of necrosis.

[0055] Where there is no conflict, the above embodiments and features described herein can be combined with each other.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A biodegradable magnesium alloy staple, characterized in that, The matrix of the anastomotic staple is a quaternary magnesium alloy of Mg-Nd-Y-Zr, and its composition by mass percentage is as follows: Nd 2.0%~4.0%, Y 0.5%~3.0%, Zr 0.3%~0.8%, unavoidable impurities total less than 0.02%, and the remainder is Mg; the structure of the anastomotic staple after firing is D-type.

2. The biodegradable magnesium alloy staple according to claim 1, characterized in that, The pre-firing structure of the staple is U-shaped, consisting of a straight crossbeam and staple legs integrally connected to both ends of the crossbeam and perpendicular to the crossbeam.

3. The biodegradable magnesium alloy staple according to claim 2, characterized in that, Before the staple is fired, the end of the U-shaped staple leg is provided with a bevel angle and a puncture tip, and the bevel angle is 30° to 45°.

4. The biodegradable magnesium alloy staple according to claim 2, characterized in that, The length of the crossbeam of the U-shaped structure before the staple is fired is 3.0 mm to 5.0 mm, the length of the staple leg is 3.5 mm to 5.5 mm, and the diameter of the staple wire is 0.2 mm to 0.4 mm.

5. The manufacturing process of a biodegradable magnesium alloy staple according to claim 1, 2, 3 or 4, characterized in that, Includes the following steps: (1) Determine the proportion of raw materials, wherein the raw materials include high-purity magnesium ingots, Mg-Nd master alloy, Mg-Y master alloy, and Mg-Zr master alloy, and prepare the raw materials according to the mass percentage of the target alloy; (2) Vacuum induction melting and casting: The prepared raw materials are placed in the crucible of the vacuum induction melting furnace, and after vacuuming, protective gas is introduced. Melting is carried out at a temperature of 720 ℃~760 ℃, with mechanical stirring for 15 minutes. Then, the mixture is poured into a preheated steel mold to obtain an alloy ingot. (3) Homogenization heat treatment: Place the above alloy ingot in a heat treatment furnace and heat it to 500°C at a heating rate of 5°C / min under a protective atmosphere. Hold it for 8 hours. After holding, take it out and air cool it to room temperature. (4) Hot extrusion and multi-pass cold drawing: the homogenized ingot is processed into an extrusion billet, heated to 350°C and held for 2 hours, and extruded into a bar in an extrusion press according to the extrusion ratio; the bar is drawn through a multi-pass die, with each drawing deformation amount of 10% to 20%, and intermediate annealing between passes to obtain a wire with a diameter of 0.2 mm to 0.4 mm; (5) Graded solution treatment and artificial aging treatment: The wire is placed in a resistance furnace and graded solution treatment under a protective atmosphere. After that, it is taken out and water-quenched to room temperature. The water-quenched wire is placed in an aging furnace and kept at 225°C for 24 hours, and then air-cooled to room temperature. (6) Stamping and forming: the air-cooled wire is cut into lengths of 3.5mm to 5.5mm, and then stamped and bent into D-shaped initial-state staples at room temperature by forming mold. After being squeezed by the stapler anvil, D-shaped closed-structure staples are formed.

6. The manufacturing process of a biodegradable magnesium alloy staple according to claim 5, characterized in that, In step (2), high-purity argon is used as a protective gas.

7. The manufacturing process of a biodegradable magnesium alloy staple according to claim 5, characterized in that, In step (4), the extrusion ratio is 18:1 and the extrusion speed is 0.5 to 2.0 m / min; intermediate annealing is carried out between passes at 300°C to 350°C for 60 minutes.

8. The manufacturing process of a biodegradable magnesium alloy staple according to claim 5, characterized in that, In step (5), the resistance furnace is tubular and the protective gas is argon; the graded solution treatment is divided into primary solution treatment and secondary solution treatment. In the primary solution treatment, the drawn rivet wire is placed in the tubular resistance furnace and heated to 480°C for 2 hours under argon protection. The secondary solution treatment involves raising the furnace temperature to 520°C and holding it for 2 hours based on the primary solution treatment. Then, the solution is removed and cooled to room temperature by water quenching at 60°C to 80°C.

9. The manufacturing process of a biodegradable magnesium alloy staple according to claim 5, characterized in that, In step (6), the surface of the initial state anastomotic staple, which is punched and bent into a "D" shape at room temperature, is ultrasonically cleaned. After cleaning, the initial state anastomotic staple is squeezed by the stapler's anvil seat, and the two staple legs curl and bend towards the center of the inner crossbeam. The ends of the two staple legs abut or overlap each other to form a D-shaped closed structure anastomotic staple.

10. The manufacturing process of a biodegradable magnesium alloy staple according to claim 5, characterized in that, The process described above prepares D-type biodegradable magnesium alloy staples.